THE INFLUENCE OF SELF-ESTEEM IN SPEAKING SKILL AT THE SECOND GRADE STUDENTS OF MAN 2 MADIUN - Samsul Arifin; Linda Pertiwi (Universitas PGRI Madiun, 2017)
Self-esteem has a key characteristics to start any action especially for speaking. From all of language skill, speaking is the notable one to make a communication run well. In this regard, the objective of this research is to describe the influence of self-esteem in speaking skill at the second grade students of MAN 2 Madiun. The sample of this research is PLCI class consisting of 30 students in the second grade of MAN 2 Madiun. The descriptive research approach is used in this study. This research was conducted by using interview and questionnaire. The collected quantitative data were analyzed by Statistical Package for the Social Sciences (SPSS) 16.0 program. The Pearson Product-moment correlation coefficient and dependent sample t-test were used to analyze the data. The results indicate that there is strong positive correlation between self-esteem and speaking skill of Senior High School students, where the correlation value is positive r= .97. The significant p= .00 < .05 which indicates that there is significant relationship between self-esteem and speaking skill. Beside that, there is also significant correlation at the level of .01 between them. In conclusion, this research shows that students self-esteem give significant influence in their speaking skill. If the level of self-esteem increases, the speaking grades of the students increase too. In line with the conclusion of this research, it is important to pay more attention to the students self-esteem in order to enhance their speaking skill.